2009
DOI: 10.1111/j.1600-0714.2008.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD146 gene expression via RNA interference reduces in vitro perineural invasion on ACC‐M cell

Abstract: These findings suggested that CD146 was an ACC-related gene and CD146 may play an important role in the carcinogenesis, progression and PNI activity of ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Cells that had invaded the Matrigel and reached the lower surface of the filter were fixed in methanol, stained with H&E, and counted as previously described. 14 In vivo tumorigenicity assays. All protocols involving animals were approved by the China Institutional Ethics Review Committee for Animal Experimentation.…”
Section: Methodsmentioning
confidence: 99%
“…Cells that had invaded the Matrigel and reached the lower surface of the filter were fixed in methanol, stained with H&E, and counted as previously described. 14 In vivo tumorigenicity assays. All protocols involving animals were approved by the China Institutional Ethics Review Committee for Animal Experimentation.…”
Section: Methodsmentioning
confidence: 99%
“…Ryschich et al identified expression of laminin in the perineural space of nerves in pancreatic cancer and increased migration and invasion of pancreatic cells on laminin substrates was observed during pancreatic cancer PNI (Ryschich et al, 2009). Recent work has also demonstrated that inhibition of melanoma cell adhesion molecule (MCAM or CD146) using short hairpin silencing RNA in an adenoid cystic carcinoma cell line decreased perineural invasion in vitro (Chen et al, 2009). …”
Section: Cell Adhesion Molecules and Perineural Invasionmentioning
confidence: 99%
“…17 Various approaches for targeting MCAM have already been investigated; antibodies against MCAM, immunization with MCAM, silencing of Mcam expression with siRNA and shRNA molecules. 18,19,20,21,22,23,24,25,26,27 The use of antibodies against MCAM has been effective in vitro in the reduction of proliferation, migration and tube formation in human endothelial cells, 18,19 and invasion in melanoma and osteosarcoma cells. 19,20 The therapy of melanoma, osteosarcoma, hepatocarcinoma, leiomyosarcoma and pancreatic tumors in mice in vivo with intraperitoneal injection of antibodies against MCAM reduced tumor growth and the formation of metastases of melanoma and osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…It reduced proliferation or survival, adhesion, migration and invasion of cells. 22,23,24,25,26 There was only one in vivo study targeting MCAM mRNA by RNA interference technology (RNAi), where the treatment of pathological angiogenesis in mice with miRNA targeting MCAM mRNA significantly attenuated neovascularization. 27 A step further in this field would definitely be the use of plasmid DNA encoding shRNA against MCAM, which allows more stable and long-lasting expression of shRNA for the maximization of therapeutic effect in comparison with siRNA delivered alone.…”
Section: Introductionmentioning
confidence: 99%